FACTORS AFFECTING THE PERFORMANCE OF LIBRARY AND INFORMATION PROFESSIONALS IN THE LIBRARIANS' LICENSURE EXAMINATION (LLE) 2006-2010, PART 2: YEAR OF GRADUATION, ACADEMIC DEGREES, AND EDUCATIONAL INSTITUTIONS - Ramos, Mila; Ananoria, Arabella; Nera, Corazon (Journal of Philippine Librarianship, 2014)
This article presents factors such as year of graduation, academic degrees, and educational institutions, that affect the performance of the LLE takers for the years 2006-2010. These factors were then correlated with the passing percentage for the years 2005-2010. It was found out that all these factors do not significantly affect performance in LLE.
Keywords: library and information science; LIS; licensure examination; philippine librarianship, professional regulation commission